Electronic Modules in an Indonesian Higher Education: Conceptualisation, Development and Application - Novi Marlena; Finisica Dwijayati Patrikha; Renny Dwijayanti (AL-ISHLAH: Jurnal Pendidikan, 2022)
One of the 21st-century learning focus is innovation on technology-integrated teaching materials. Teaching materials are often ineffective because lecturers are the primary source of learning activities, resulting in student dependency. This research aimed to develop a Marketing Management E-Module following the feasibility assessment by the experts and measure the effectiveness of the Marketing Management E-Module.  The E-Module adopted a 4-D development model (Define, Design, Develop, Disseminate). The data collection was through experts' review and validation tests (material experts, media experts, and linguists) and pre-test and post-test questions. The results showed that the development of the Marketing Management E-Modules is very feasible, shown by the experts' validation assessment of 89.16%. Moreover, Marketing Management E-Module is practical since the student learning outcomes increased after utilizing Marketing Management E-Module.